2018
DOI: 10.17240/aibuefd.2018..-431461
|View full text |Cite
|
Sign up to set email alerts
|

Sinif Öğretmenleri̇ni̇n Öğrenme Güçlüğünün Tanimina İli̇şki̇n Görüşleri̇

Abstract: Öğretmenlerin öğrenme güçlüğü hakkındaki görüş ve bilgileri, öğrenciyi tanılamak, doğru yönlendirmeyi yapmak ve değerlendirmek için de önem taşımaktadır. Bu bağlamda sınıf öğretmenlerinin öğrenme güçlüğün ne olduğu hakkındaki görüşlerinin belirlenmesi bu konudaki eksikliklerinin ortaya konulması açısından kritiktir. Sınıf öğretmenlerinin öğrenme güçlüğünün ne olduğuna yönelik görüşlerinin belirlenmesinin amaçlandığı bu çalışmada nitel araştırma desenlerinden "durum çalışması" kullanılmıştır. Çalışmanın katılım… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
1
5
0
9
Order By: Relevance
“…Teachers did not provide any information about the field of the variable and how it occurs. This result supports the research results expressing that primary school teachers do not have enough information about the features of the students with LD (Aladwani & Al Shaye, 2012;Altun & Uzuner, 2016;Balcı, 2019;Doğan, 2013;Fırat & Koçak, 2018;Lingeswaran, 2013). For example, Başar and Göncü (2018) found that primary school teachers had misconceptions about learning disabilities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Teachers did not provide any information about the field of the variable and how it occurs. This result supports the research results expressing that primary school teachers do not have enough information about the features of the students with LD (Aladwani & Al Shaye, 2012;Altun & Uzuner, 2016;Balcı, 2019;Doğan, 2013;Fırat & Koçak, 2018;Lingeswaran, 2013). For example, Başar and Göncü (2018) found that primary school teachers had misconceptions about learning disabilities.…”
Section: Discussionsupporting
confidence: 85%
“…al., 2005;Moothedath & Vranda, 2015;Saravanabhavan & Saravanabhavan, 2010;Wright, 2008). Although there are few studies focusing on the opinions of Turkish teachers on LD (Altuntaş, 2010;Çakıroğlu, 2015;Doyran & Canca, 2013;Fırat & Koçak, 2018;Özabacı & Ergün-Başak, 2013;Polat, 2013;Yangın, Yangın, Önder, & Şavlığ, 2016), the number of studies focusing on the opinions of primary school treachers on LD and what they would do when they encounter a student with LD is limited.…”
mentioning
confidence: 99%
“…Findings obtained from the research explained how teachers work with students with special needs, in which areas they experience inadequacy, and feel inadequate in determining their weaknesses and strengths. In studies that examine teachers' competencies related to learning disability concept, it is revealed that teachers have misconceptions about learning disability and sub-dimensions of learning disability, definitions of learning disability are quite superficial and few of them emphasize areas that have difficulty in defining learning disability (Başar & Göncü, 2018;Fırat & Koçak, 2018). Teaching and Learning International Survey (2010) according to what teachers are special needs students are missing the conclusions reached regarding maximum will be made.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Araştırmadan elde edilen bulgular öğretmenlerin özel gereksinimli öğrencilerle nasıl çalışacaklarını, hangi alanlarda yetersizlik yaşadıklarını, zayıf ve güçlü yanlarını belirleme konularında kendilerini yetersiz hissettiklerini açıklamışladır. Öğretmenlerin öğrenme güçlüğü kavramına ilişkin yeterliliklerinin incelendiği çalışmalarda öğretmenlerin öğrenme güçlüğü ve öğrenme güçlüğünün alt boyutları hakkında kavram yanılgılarına sahip oldukları, öğrenme güçlüğü tanımlarının oldukça yüzeysel olduğu ve çok azının öğrenme güçlüğünü tanımlarken güçlük yaşanan alanlara vurgu yaptığı ortaya çıkmıştır (Başar ve Göncü, 2018;Fırat ve Koçak, 2018). Uluslararası Öğretme ve Öğrenme Araştırması Türkiye Ulusal Raporuna (2010) göre öğretmenlerin özel gereksinimli öğrencilere neler yapılacağı konusunda en fazla eksik kaldığı sonucuna ulaşılmıştır.…”
Section: Sonuç Ve Tartışmaunclassified
“…yaklaşık 60 yıllık süreçte öğrenme güçlüğünün özel eğitim alanında en sık duyulan kavramlardan biri haline geldiğini söylememiz mümkündür(Fırat ve Koçak, 2018). Amerika Birleşik Devletleri'nde en son çıkan raporlardan birinde, Engelli Bireyler Eğitim Yasası (The Individuals ith Disabilities Education Act; IDEA) kapsamında özel eğitim hizmetleri alan 3 21 yaş arası öğrenci sayısının milyon olduğu ve bu öğrencilerin yüzde 34'ünün öğrenme güçlükleri olan öğrencilerden oluştuğu belirtilmiştir (McFarland vd., 2019).…”
unclassified